2003
DOI: 10.1046/j.1365-2486.2003.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in arid‐land forest

Abstract: Rising atmospheric CO2 concentrations may lead to increased water availability because the water use efficiency of photosynthesis (WUE) increases with CO2 in most plant species. This should allow the extension of afforestation activities into drier regions. Using eddy flux, physiological and inventory measurements we provide the first quantitative information on such potential from a 35‐year old afforestation system of Aleppo pine (Pinus halepensis Mill.) at the edge of the Negev desert. This 2800 ha arid‐land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(149 citation statements)
references
References 37 publications
11
135
3
Order By: Relevance
“…Further, Giannecchini (2007) observed that dependence on subsistence farming is an indication of land based activities being fundamental to household livelihoods. According Grunzweig et al (2003), over reliance on crop cultivation leads to more tracks of land to be cleared causing landcover changes. These changes escalate conflicts in the provision food, fuel and roughage on which the livelihoods of poor people critically depends (Bolwing & Odeke, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Giannecchini (2007) observed that dependence on subsistence farming is an indication of land based activities being fundamental to household livelihoods. According Grunzweig et al (2003), over reliance on crop cultivation leads to more tracks of land to be cleared causing landcover changes. These changes escalate conflicts in the provision food, fuel and roughage on which the livelihoods of poor people critically depends (Bolwing & Odeke, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to global and regional climate models, Mediterraneantype ecosystems (MTEs) will suffer longer and more intense droughts as a result of (1) increasing temperature and decreasing rainfall (Hoerling et al, 2011), (2) a change in largescale circulation conditions (Kjellström et al, 2013), and (3) the persistence of heat wave anomalies (Jaeger and Seneviratne, 2011). In MTEs, drought is already the prevailing constraint on the net ecosystem productivity (NEP) (Allard et al, 2008;Grünzweig et al, 2003). This sink strength is likely modified by the differential sensitivity to water limitation of leaf photosynthesis and whole-tree respiration, and of the C allocation to short-and long-lived pools.…”
Section: S Rambal Et Al: Drought and C Partitioningmentioning
confidence: 99%
“…Among the numerous types of ecosystems, forest ecosystems play a crucial role in the global carbon budget [1][2][3][4][5][6]. In Central Asia, desert riparian forest ecosystems along large river systems, such as the Amu Darya, Syr Darya, and Tarim River, store a large amount of carbon in the aboveground (leaves, branches, and stems) and belowground (roots) biomass and provide the main biomass resources for human wellbeing in those continental arid regions [7][8][9][10][11]. Due to the extremely arid climate conditions of these regions, the productivity of riparian forest ecosystems is highly dependent on groundwater and soil moisture availability supplied by inland river water flow [12].…”
Section: Introductionmentioning
confidence: 99%